A Brief Overview of the Development on the Foreign Exchange Market in China: From 2018 to 2022 - He Junlin; Wen Baoyu; Du Yulun (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Transactions in the foreign exchange market determine the value of one currency relative to another, and in the present day of globalization, the foreign exchange market in each country has been the focus of scholars. However, few scholars seem to have combed through the development of Chinese foreign exchange market and the hot spots and directions of research in the last five years. Therefore, this study uses keyword co-occurrence and clustering analysis of 177 literature from Scopus and Web of Science were conducted using Citiespace software. The results show that the topics that scholars have focused on in the last five years include "exchange rate," "market," "China,” etc. In addition, this study considers that the research directions of scholars are mainly divided into three categories.